Kedudukan Syariat Islam di Aceh dalam Sistem Hukum Indonesia - Hasan Basri (Kanun Jurnal Ilmu Hukum, 2011)
ABSTRACT: Dissatisfaction that occurs in a social community of injustices in the treatment due to politics, economics and law has led to social conflicts that lead to a variety of social behavior in the context of civic life. One of the social perubahana in the application of the law of politics in Indonesia since the end of the New Order regime, and the period of reform can be seen in efforts to address the phenomenon of Indonesian statesman disintegritas arising in Aceh so that eventually gave birth to Law Number 11 Year 2006 about the government of Aceh, the Act has brought great changes to the law in force in Aceh. The birth qanu-qanun and implementation efforts of Islamic law in Aceh has extended the range deversitas kaffah laws of the Republic of Indonesia with the 1945 constitutional system. On the one hand the notion as a group of people about the rights of autonomy that is so vast and highly principled for the Aceh region of Act No. 11 of 2006, who were later considered to be one of the basic implementation of Islamic sharia in Aceh kaffah is a part of Indonesia's legal system. It is certainly not independent of the legal structure, legal substance and legal culture contained in the state unitary Republic of Indonesia. The Status of Islamic Law in Aceh in Indonesian Legal System